Meningkatkan Daya Ingat Tajwid melalui Mnemonic Learning - Fathor Rozi; Nailus Sa'adah; Nur Hayati (FONDATIA, 2022)
Learning the science of recitation which has many kinds is not an easy matter for students, especially if the teacher only uses the lecture and memorization method which makes students more bored so that it is difficult to understand and memorize the material. This study aims to examine the Mnemonic Learning method used in recitation lessons. The research approach used is descriptive qualitative case study type. The research location is in MI Darussalam Sumberejo Paiton Probolinggo, especially in the Tahsinul Qur'an program. The data collection technique used is observation or observation and interviews. While the data analysis techniques used are data reduction, data presentation, and drawing conclusions. From this research, it is known that it is easier for students to remember material for a long time without feeling pressured and bored because of the songs, acronyms, and mind maps used in the Mnemonic Learning method. The implication is that teacher creativity is needed in developing methods (singing, acronyms, concept maps, games, etc.) that are in accordance with the learning material so that students can more easily capture and remember the material because they feel happy and not burdened.